TINDAKAN HUKUM PEMERINTAH KOTA DUMAI DALAM MEMUTUS PENYEBARAN CORONA VIRUS DISEASE 2019 (COVID-19) - Siti Desma Syahrani; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The legal actions of the dumai city government are the rules or regulations made by the dumai city government in an effort to break the spread of the covid-19 of the 5 (five) legal actions of the mayor of dumai, the mayor of dumai, the city's handbill of dumai, the city government plan of dumai and the city's permission of dumai. The problem with this study is that the increase in the incidence of the covid-19 across the city of dumai, law enforcement that implires jeria has not been effective in enforcing and lack of communication with the city's dumai government, and the lowering of public legal awareness to adhere to health protocol. The purpose of this study is to find out how the legal action of the city's dumai government in breaking the spread of the covid-19.The research approach used is a qualitative approach, this type of research is descriptive. The research location is in Dumai City, precisely at the Health Service, Dumai City Covid-19 Task Force, Dumai City Secretary, Dumai City Satpol PP, Resort Police, and the community especially business actors. And the data collection technique is done by interview and documentation. The results of this study are that the implementation of the Dumai City Government Legal Action in deciding the spread of Covid-19 has gone quite well, this is marked by the decline in Covid-19 cases in Dumai City. However, it is undeniable that there are still obstacles in its implementation, namely the Dumai City Government Legal Action which does not contain sanctions for violators, namely Circulars and the level of legal awareness of the community is still low in complying with health protocols.Keyword: Government Legal Action, Covid-19, Dumai